Prognostic importance of metabolic tumor parameters on initial FDG-PET/CT in patients with isolated infradiaphragmatic Hodgkin’s lymphoma - Alagoz, Engin; Okuyucu, Kursat; Ince, Semra; Ozgur, Gokhan; Ozmen, Ozlem; Karacalioglu, Alper Ozgur; Ozturk, Mustafa; Arslan, Nuri (Vojnosanitetski pregled, 2017)
Background/Aim. Isolated infradiaphragmatic lymph node involvement is not common and makes up 5–13% of stage I-II Hodgkin’s lymphoma. Important subjects about prognostic factors and optimal treatment of isolated infradiaphragmatic Hodgkin’s lymphoma (II HL) have not been clearly defined. We aimed to evaluate the prognostic value of metabolic tumor indices on initial 18-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) through quantitative PET/CT parameters together with the classical predefined risk factors for patients with II HL. Methods. This retrospective cohort study conducted between 2004 and 2015 included 21 patients for whom FDG-PET/CT were requested for primary staging. Quantitative PET/CT parameters (maximum standardized uptake value – SUV max) average standardized uptake value – SUV mean, metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were used to estimate disease-free survival and overall survival. Results. Univariate Cox regression analysis was performed for all potential risk factors impacting metastasis/recurrence of the disease. Factors which had values of p < 0.2 after univariate analysis (sex, age, stage, bulky disease, SUV max, SUV mean, MTV, TLG) were processed with the multivariate model. Sex, TLG and bulky disease were found to be statistically significant risk factors for prognosis of outcome in patients with IIHL after multivariate analysis. Conclusion. The existence of bulky disease at the diagnosis and high TLG values on primary staging by FDG-PET/CT are potential risk factors for both disease-free survival and overall survival in Hodgkin’s lymphoma with isolated infradiaphragmatic lymph node involvement.
Keywords: hodgkin disease; lymph nodes; diaphragm; positron- emission tomography; fluordeoxyglucose f18; tomography; x-ray computed; prognosis